ANALISIS BIAYA MAKAN TERHADAP KETERSEDIAAN MAKANAN SERTA TINGKAT KECUKUPAN GIZI SANTRI DI PONDOK PESANTREN DARUL ARQAM GARUT - Sudrajat, Ahmad Sahl; Sinaga, Tiurma (GIZI INDONESIA, 2016)
The general objective of this study was to analyze the cost control towards the food availability and the nutritional adequacy level of the female santri in Darul Arqam Boarding School, Garut. The study was held in April until June 2015 using the cross-sectional study. The sample was taken purposively with a total of 86 people. The result showed that the food service management was able to manage over 88.09 percent of total funds. The pearson correlation showed that there was no significant correlation (p>0,05) between the cost with the energy, protein, fat, vitamin C, and iron availabilities. There was a significant correlation (p<0.05) between the cost and the carbohydrate availability. The energy and nutrients have not reached the nutritional requirement of the students. Thus, the adequacy level of the energy, protein, vitamin C, and iron was categorized as severely deficit. The carbohydrate adequacy level classified as normal, while the fat adequacy level classified as excessive. The study suggested the management of the Boarding School to review the existing budget for meals in order to ensure the menu could meet the nutritional requirement of the santri. Beside, efforts need to be taken to ensure improved balanced and healthy meal available for the santri.